Perangkap Hama Tenaga Surya - Sumarwan (Jurnal Riset Daerah, 2021)
Activities aimed at community service in agriculture to reduce the use of pesticides with an effective, cheap and environmentally friendly pest control system. Almost all insects that are active at night have the capacity to respond to light, the visual organs of animals are sensitive to wavelengths that are close to ultraviolet (UV) light. Has successfully designed and manufactured a pest trapping device with UV light, which comes from batteries and solar cells. To make it easier to use farmers, the tool is equipped with a controller so that charging the battery during the day and turning on the lights at night works automatically. Based on the results of the tests that have been carried out, the tool can function properly, that is, the battery charging takes place normally and at sunset, the UV lamp automatically lights up. Based on the test results, the tool is functioning properly and can trap pests that are usually active at night. And the pests will die in a bucket filled with detergent mixed water. And farmers can change the detergent water if the bucket has many dead pests or every 3 to 5 days. Lamp needs 1 hectare of land: 12 units of food crops (rice, soybeans, corn), 30 units of horticultural crops (brambang, chilli, cabbage) 30 units, plantation crops (oranges, papaya, banana) 15 units or the need to adjust the land layout conditions